Odpowiedzi

Najlepsza Odpowiedź!
2009-11-21T19:32:43+01:00
C) 4x³ - 8x² + 12x - 2x³ - 6x² + 2x = 2x³ - 14x² + 14x = -128 - 224 - 56 = -408
d) 6a²b - 2ab + 10a - 6a²b + 9ab + 12b = -6ab +10a + 12b = 18 - 10 + 36 = 44
2009-11-21T19:34:31+01:00
C)4(׳-2ײ+3×)-2×(ײ+3×-1) dla ×= -4

4(׳-2ײ+3×)-2×(ײ+3×-1) = 4׳ -8ײ+ 12x-2׳-6ײ-2x=
2׳- 14ײ +10x= 2 * (-4)³- 14* (-4)² +10 * (-4)=
= 2 * (-64) - 14* 16 -40= -128 - 224- 40= - 392

d)2a(3ab-b+5)-3b(2a²-3a-4) dla a= -1, b=3

2a(3ab-b+5)-3b(2a²-3a-4)=
= 6a²b- 2ab +10a - 6a²b+ 9ab+12b=
= 7ab+10a+12b= 7*(-1)*3 + 10*(-1)+ 12* 3=
=-21-10+36= -31 + 36= 5
2009-11-21T19:39:27+01:00
C)4(׳-2ײ+3×)-2×(ײ+3×-1) dla ×= -4

4(׳-2ײ+3×)-2×(ײ+3×-1) = 4x³ - 8x² + 12 x - 4x³ + 6x² - 2x = -2x² + 10x =
= -2 * (-4)² + 10 * (-4) = -32 + (-40) = -32 - 40 = -72

d)2a(3ab-b+5)-3b(2a²-3a-4) dla a= -1, b=3

2a(3ab-b+5)-3b(2a²-3a-4) = 6a²b - 2ab + 10a - 6a²b - 9ab - 12b =
= -11ab + 10a - 12b = -11*(-1)*3 + 10*(-1) - 12*3 = 33+ (-11) - 36 = 33-11-36 =
= -14